A Study on Cluster Behavior by Company Size in the Korean Stock Market - Seong Hyun Lee(이성현); Wonseok Kang(강원석) (신산업경영저널, 2024)
Herding behavior refers to a phenomenon in which certain stocks or assets show similar characteristics or tend to move together in the stock market, which can often occur in similar industries, sectors, and investor groups. In this study, we analyzed whether herding behavior occurred among stocks listed on the stock market from August 2018 to November 2021, and divided the size of stocks by market capitalization to find out the difference in the degree of herding behavior depending on the size of the company. The results showed that there was no significant clustering behavior for large, mid, and small-cap stocks. However, the clustering analysis shows that the clustering of large-cap stocks in market capitalization is weaker than the clustering of mid-cap and small-cap stocks. In addition, the cross-sectional scatterplot is reduced when market returns are extremely high or low, suggesting a new characteristic of clustering. KCI Citation Count: 0